Part 4. (1st June 2015) - Stengers, Isabelle; Davis, Christine; Lyall, Scott; Serres, Michel; Massumi, Brian; Didi-Huberman, Georges
Entries: Sea Noise, Sensa, Proteus, Black Glass, Techniques of Existence, Prehension, Puffs of Existence, The Close-Up, Pan de Mur Jaune, Concrescence, The Infra-Thin. Includes text by Isabelle Stengers, Christine Davis, Scott Lyall, Michel Serres, Brian Massumi, Georges Didi-Huberman. Artworks by Scott Lyall, Glenn Ligon, Annie Besant and Charles Leadbeater, Annika von Hausswolff, Scott Treleaven, Diane Morin.